The Role of Artificial Intelligence in the Digital Transformation of Education in the Era of Society 5.0 - Husaini Husaini; Diana Suksesiwaty Lubis; Laila Qadriah; Patriandi Nuswantoro (Westscience Press, 2025)
The rapid advancement of digital technology has accelerated the transformation of education systems, particularly through the adoption of artificial intelligence (AI) in the era of Society 5.0. This study aims to analyze the role of artificial intelligence in driving the digital transformation of education in Indonesia. A quantitative research approach was employed using survey data collected from 85 respondents involved in the education sector. Data were gathered through a structured questionnaire using a Likert scale and analyzed with SPSS version 25. The analysis included descriptive statistics, validity and reliability testing, and simple linear regression. The results indicate that artificial intelligence has a positive and statistically significant effect on the digital transformation of education. The regression analysis shows that AI explains 55.1% of the variance in digital transformation, highlighting its substantial contribution to improving learning personalization, administrative efficiency, and data-driven decision-making in educational institutions. Despite these positive outcomes, challenges related to digital infrastructure and human resource readiness remain. This study provides empirical evidence supporting the strategic importance of artificial intelligence in advancing educational transformation and offers insights for policymakers and educational institutions in aligning digital education strategies with the goals of Society 5.0 in Indonesia.